Isolated single lobe hyperplasia of the thyroid gland, presenting as anterior mediastinal mass, detected on positron emission tomography-computed tomography scan - Nitin Gupta; Dharmender Malik; Ritu Verma; Sunila Jain (World Journal of Nuclear Medicine)
We report a case who presented with facial swelling and breathlessness. Recent chest X-ray was suggestive of soft-tissue in the mediastinum. In view of the suspicion of mass being neoplastic, the patient was referred for positron emission tomography-computed tomography (PET-CT) scan. Whole-body fluorodeoxyglucose (FDG) PET-CT scan revealed a mildly FDG-avid large lobulated soft-tissue mass in the anterior mediastinum, seen to arising from right lobe of the thyroid gland, extending into the right hemithorax. Histopathological examination of the mass was compatible with adenomatous hyperplasia of the thyroid. Here, we report an unusual case of isolated single lobe hyperplasia of the thyroid gland, masquerading as an anterior mediastinal mass.